EXPLORING THE NEXUS OF PROJECT-BASED LEARNING, ECONOMIC FACTORS, AND MARKETING SUCCESS: AN INTEGRATED EXAMINATION - Ahmad Talib; Rosnani Said; Fuadah Johari; Iyad Abdallah Al- Shreifeen (Adisam Publisher, 2024)
This paper undertakes a comprehensive exploration of the intricate interplay between project-based learning (PBL), economic variables, and marketing outcomes, delving into their multifaceted intersectionality. By meticulously examining how economic conditions influence the implementation of PBL initiatives and subsequently affect marketing efficacy, this study aims to offer valuable insights beneficial to educators, policymakers, and marketers. Employing a multifaceted analytical framework, we delve into the nuanced ways in which socioeconomic status impacts the adoption and effectiveness of PBL strategies, and how these strategies, in turn, shape marketing approaches and outcomes. Drawing on both empirical research and theoretical constructs, we illuminate the complex dynamics between education, economics, and marketing, providing a holistic perspective that reveals avenues for enhancing educational practices and optimizing market performance.